PENGARUH PARTISIPASI ANGGARAN, EVALUASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING - Kusuma , IC; Lasmana, A; Afif , MN; Hambani , S; Faniska, NS (Jurnal Akunida, 2021)
This study aims to determine the influence of budget participation, budget evaluation, clarity of budget targets partially and simultaneously on managerial performance with organizational commitment as moderating variables. The research method used is quantitative method with causality relationship approach (causality). The object in this study is officials in the Bogor City device environment related to the process of drafting and implementing budgets and finances. The research sample of 30 OPD using purposive sampling technique with respondents amounted to 183. Data analysis method using multiple regression analysis and moderated regression analysis (MRA) with the help of SPSS 21.0 software program. The results explain budget participation, budget evaluation, and budget clarity both simultaneously and partially positively and significantly affect managerial performance. Meanwhile, the organization's commitment to moderate the relationship between independent variables to dependent variables.